The Responses of Injection Pressure and Fracture Width during Height Extension in Sand-Mud Interbed Reservoirs in the Dongsheng Gas Field. (28th November 2021) - Wang, Di; Wang, Haibo; Li, Fengxia; Chen, Fuhu; Zhu, Xinchun
Abstract : The Dongsheng gas field is characterized by low porosity and low permeability. Its principal producing reservoir is the H-1 zone, belonging to the Lower Shihezi Formation. Sand is the main lithology in the H-1 zone, while mud interlayers are also well developed in a vertical direction. As a result, the reservoir is a sand-mud interbed, which brings difficulty to fracture height extension. In order to understand the process of fracture height growth in a sand-mud interbed reservoir and obtain the responses of injection pressure and fracture width during a hydraulic fracturing, a hydromechanical-coupled model is established. Mud interlayers are fully considered and a cohesive zone model is adopted to deal with fracture propagation. Numerical results show that the fracture extends quickly to the sand-mud interface after initiation and breaks through rather than propagating along the interfaces. Pressure and width both increase continuously when fracture propagates in the mud interlayer. High-viscosity and high-injection rates are helpful for the fracture to break through the mud interlayer, especially at an early period. When the mud interlayers are asymmetric, pressure and width fluctuate several times once fracture propagates inside and breaks through the mud interlayer. Perforations close to the thinner mud interlayer can increase the fracture width and reduce fracturing risks.